COMPARATIVE CHARACTERISTIC OF TOURIST POTENTIAL OF MUSEUMS OF KRASNODAR REGION - Svetlana V. Kirilicheva; Anatoly A. Filobok; Vera V. Minenkova (Юг России: экология, развитие, 2017)
Aim. The article describes the tourist potential of two large museums of the Krasnodar Territory, the Krasnodar State Historical and Archaeological Museum-Reserve named after E.D. Felitsyn and Krasnodar Regional Art Museum named after F.A. Kovalenko. Much attention is paid to the classification of museums in the Krasnodar Territory. Methods. In the study were used a comparative-geographical method, a systematic approach, an analysis of statistical-mathematical materials and an analysis of the leisure profile of citizens. Findings. A comparative assessment of the potential of two large museums of the region is given. We also conducted an analysis of the survey data of the leisure profile among the townspeople in the city of Krasnodar in order to identify which of the museums is more popular. The main indicators such as the number of storage units, the total exposition and exhibition area, the number of sightseeing visits and mass events, the number of educational programs and exhibitions, the number of employees were examined and analyzed. Distinctions between museums are also noted. Conclusions. An analysis of these data showed that both museums have sufficient tourist potential to represent the city and get acquainted with the city through museums. The results of an analysis of events held in museums to attract visitors are presented. The sufficient tourist potential of two large museums for representation of the city and region is defined. The directions for their development as objects of tourism are proposed.